Chapter Gesture and Movement Indices of Presence - Popat, Sita (PETER LANG LTD International Academic Publishers, 2017)
Three players bring their avatars to the same in-game location to start a quest together. As they arrive, the gnome bounces on the spot and waves. The elf throws back her head in laughter before dancing with a provocative hip sway. The human salutes smartly and bows. Each of these gestures communicates information about the avatars themselves and about the interaction choices of the players controlling them. An avatar's movement includes a range of motions, from programmed gaits and postures to the ways in which the avatar moves in and through virtual space as guided by the player. Gestures are a subset of this movement -- a specific kind of motion that encodes personal, social, and cultural information. Gestures can be decoded by others who share an understanding of the relevant codes, communicating information about intentions, emotions, and responses to events and to other people. Gesture and movement can play a key role in avatar-mediated relationships-both in interactions with other players and in information exchanges between players and their own avatars. The importance of these conveyances may be intensified in immersive gaming as an avatar's digital body becomes more closely aligned with a player's physical body, with the potential for influences on the player's embodied experience.